2012
DOI: 10.5009/gnl.2012.6.1.64
|View full text |Cite
|
Sign up to set email alerts
|

The Miss Rate for Colorectal Adenoma Determined by Quality-Adjusted, Back-to-Back Colonoscopies

Abstract: Background/AimsColonoscopy is considered to be the gold standard for detecting adenomatous polyps. Polyps are missed during colonoscopic examination at a rate that varies from 6% to 27%. The adenoma miss rate affects colonoscopic surveillance intervals and procedural quality. We aimed to assess the adenoma miss rate and the variables affecting the rate using same-day, quality-adjusted, back-to-back colonoscopies.MethodsThis prospective study was performed at a single institution and included 149 patients. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
134
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 28 publications
11
134
1
2
Order By: Relevance
“…Other studies found that interval cancer patients tend to be older although some of those same studies found that interval cancers were more prevalent in women than in men, which we did not find in our cohort. 8,14,20,21 Our analysis corroborates the findings by Kaminski et al, 11 Nakao et al, 22 and Cooper et al, 12 that patients aged 60 years and older are more likely to develop an interval cancer. There were no differences in the cancer staging for these older patients, however.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Other studies found that interval cancer patients tend to be older although some of those same studies found that interval cancers were more prevalent in women than in men, which we did not find in our cohort. 8,14,20,21 Our analysis corroborates the findings by Kaminski et al, 11 Nakao et al, 22 and Cooper et al, 12 that patients aged 60 years and older are more likely to develop an interval cancer. There were no differences in the cancer staging for these older patients, however.…”
Section: Discussionsupporting
confidence: 95%
“…Studies have found miss rates of 5% to 16.8% for polyps, with smaller polyps being missed more often, and advanced adenomas being missed in 5.4% of colonoscopies. [7][8][9] Population-or clinical registry-based studies suggest that interval colon cancers account for 3% to 9% of cancer patients but will increase as screening programs extend to more people. [10][11][12] We began monitoring our patient population for interval cancers as part of an institutional quality management program and to improve our understanding of the characteristics of the patients, and the procedures.…”
Section: Introductionmentioning
confidence: 99%
“…However, colonoscopy is not perfect in every respect. The screening colonoscopy usually accompanies with high polyp miss rate, ranging from 6% to 28% (8)(9)(10)(11)(12). Even in quality-adjusted back-to-back colonoscopies under the circumstances of adequate withdrawal time, good bowel preparation and high cecal intubation rate, the miss rate for polyps may still reach 17% (11).…”
Section: Discussionmentioning
confidence: 99%
“…106 In a study conducted in Korea, colonoscopic withdrawal time and polyp detection rates of gastroenterology fellows were also significantly correlated. 107 However, because the length, angulations, and degree of bowel preparation can vary by patients and adenoma detection abilities differ by endoscopist, colonoscopic withdrawal time cannot be the only way to assess the quality of a colonoscopy. The most important quality metric is the adenoma detection rate of each endoscopist.…”
Section: ) Colonoscopymentioning
confidence: 99%